PENGARUH MODAL DAN E-COMMERCE TERHADAP PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) (STUDI KASUS PADA USAHA MEUBEL DI KABUPATEN KAUR) - Satiya Handayani; Ummul Khair (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This research aims to determine the influence of business capital and E-Commerce on the development of furniture MSMEs in Kaur Regency. The type of research carried out in this research is quantitative research. The data used in this research uses primary data, namely by distributing questionnaires to business actors. The sampling technique is because the population is not greater than 100 people, the author took 100% of the population in the furniture business in Kaur Regency, namely 45 business actors. In this way, the entire population without having to draw a research sample as a unit of observation is called a census technique. The analysis method used is multiple linear regression analysis. The research results show that there is an influence of capital (X1) on the development of MSMEs (Y) of 0.009, thus Ho is rejected and Ha is accepted and there is an influence of E-Commerce (X2) on the development of MSMEs (Y) of 0.003, thus Ho is rejected and Ha is accepted. Keywords: Capital, E-Commerce, MSMEs, Furniture Business